Colorimetric analysis of dental porcelains: effects of the background color - Rodrigues, C. S. [UNESP]; Lenz, J. M.; May, L. G.; Jacques, L. B. (FapUNIFESP (SciELO), 2022)
This study evaluated how the background (white or gray) affects the color parameter measurements and color difference calculations (∆Eab and ∆E00) of dental ceramics. Disc-shaped feldspathic ceramic specimens were prepared with two shades (enamel and dentin) and stained in red wine (7-day immersion). A spectrophotometer was used to perform color measurements (CIEL*a*b* coordinates) over gray and white backgrounds after the specimen preparation and after staining. The color difference was calculated with CIEDE2000 (ΔE00) and CIELAB (ΔEab) formulae. Initial L*a*b* coordinates, ΔE00, and ΔEab data were analyzed with t-tests separately for each ceramic shade. White background led to higher values of L* and b* coordinates from the enamel shade, and of L*, a*, and b* coordinates from the dentin shade. However, ΔE00 and ΔEab results from white and gray backgrounds were similar in both ceramic shades. Therefore, background color did not affect the color difference results of the slightly stained feldspathic ceramic samples.
Keywords: CIEL*a*b* system; Color; Dental ceramic